1990
DOI: 10.1037/0278-7393.16.6.1033
|View full text |Cite
|
Sign up to set email alerts
|

Repetition priming of words and pseudowords in divided attention and in amnesia.

Abstract: Repetition priming of novel stimuli (pseudowords) and stimuli with preexisting representations (words) was compared in two experiments. In one, 19 normal male subjects performed a lexical decision task with either focused or divided attention. In another, lexical decision performance was compared between 8 male Korsakoff patients and 8 alcoholic control subjects. In control conditions, repetition speeded responses to both stimulus types. Experimental conditions that minimized the contribution of episodic memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
86
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 55 publications
9
86
0
Order By: Relevance
“…Priming was significantly reduced for "no" relative to "yes" verification responses. Reduction or elimination of priming for "no" responses is a common phenomenon on the categorycued verification test (Vaidya et aI., 1997, Experiment 6) as well as on other tests, such as lexical decision (M. E. Smith & Oscar-Berman, 1990). Most importantly, however, the magnitude of priming for "yes" and "no" verification responses did not vary by stimulus format or encoding condition.…”
Section: Discussionmentioning
confidence: 98%
“…Priming was significantly reduced for "no" relative to "yes" verification responses. Reduction or elimination of priming for "no" responses is a common phenomenon on the categorycued verification test (Vaidya et aI., 1997, Experiment 6) as well as on other tests, such as lexical decision (M. E. Smith & Oscar-Berman, 1990). Most importantly, however, the magnitude of priming for "yes" and "no" verification responses did not vary by stimulus format or encoding condition.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, under some conditions the amount of priming is equivalent for full and dividedattention encoding conditions (Jacoby et aI., 1989;Parkin et aI., 1990;Russo & Parkin, 1993;Smith & Oscar-Berman, 1990). This equivalence has been demonstrated for the word-fragment completion test (Parkin et aI., 1990), the picture-fragment completion test Russo & Parkin, 1993), lexical decision (Smith & Oscar-Berman, 1990), and the famejudgment task developed by Jacoby and his colleagues (Jacoby et aI., 1989). In these same studies, dividing attention reduced performance on direct tests, such as recognition memory (Parkin et aI., 1990) and recall tests Russo & Parkin, 1993).…”
mentioning
confidence: 83%
“…Although several of the studies mentioned above found dissociations between indirect and direct memory tests, there were typically several differences between the memory tests besides test instructions (Parkin et aI., 1990;Russo & Parkin, 1993;Smith & Oscar-Berman, 1990). In order to determine whether the differentiating effects of divided attention are due to the direct/indirect difference, one needs to compare performance on two memory tests that are identical in all regards except test instructions (Neely, 1989;Schacter, Bowers, & Booker, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ifsubjects are engaged in a concurrent attentiondemanding task when list items were available for inspection, their subsequent performance on an explicit episodic task is much lower than that under full-attention conditions. In contrast, studies have shown that concurrent processing tasks have no effect on perceptual repetition priming (Parkin, Reid, & Russo, 1990;Smith & Oscar-Berman, 1990). Manipulations of age and divided attention have suggested that perceptual repetition priming is not dependent on the allocation of attention.…”
mentioning
confidence: 96%